Resiliente Lokalsamfunn i Troms. Betydningen av sosial kapital i håndtering av kriser - Øien, Anne (UiT Norges arktiske universitet, 2024)
This thesis explores the role of social capital in enhancing resilience within small communities in Northern Norway, focusing on the municipalities of Bardu and Karlsøy. Employing a mixed-methods approach with a qualitative emphasis, the study examines how bonding, bridging, and linking social capital contribute to community resilience during different phases of crises: preparation, response, and recovery. Data were collected through in-depth interviews, a survey, and a review of relevant literature, offering insights into the interplay between local networks, trust, and resource mobilization. The findings highlight the critical role of social capital in facilitating adaptive capacity, collective action, and sustainable recovery in rural communities with limited resources. The thesis argues that strengthening social capital is key to building resilient societies, while also addressing structural and cultural factors that may hinder its development.